The Use of Audio Visual-Based Learning Media to Improve Arabic Learning Outcomes - Angga Pratama; Fahru Rozi (Edumaspul: Jurnal Pendidikan, 2024)
The use of learning media is a necessity for teachers in running the learning wheel. The presence of learning media is very important because it can help teachers outline learning concepts in real life in the classroom. Learning Arabic at MTS Darul Mafaza has a very important role for the development of language skills both reading, writing, listening, and speaking. This study uses a quasi-experimental research method with a location at MTS Darul Mafaza. The subject of the study was grade VIII students of MTS Darul Mafaza, as many as 40 students consisting of 20 students for class A as the control class and 20 students for class B as the experimental class. The results of the study show that the effectiveness of audio-visual learning media in Arabic language learning can increase better results compared to learning without using audio-visual media. This is shown by the score on the learning outcome test (posttest) superior to (pretest). The pretest results from the experimental class were obtained with an average of 45.25 and for the control class of 41.25. For the posttest results of the experimental class, the average was 70.25 and for the control class was 53.65. In conclusion, the effectiveness of audio-visual learning media in improving student learning outcomes in Arabic language learning in grade VIII students of MTS Darul Mafaza can significantly differentiate student learning outcomes.